Integrated Model For Tailoring Gamified Information Systems In Higher Education Institutions In A Developing Economy - Ofosu-Ampong, K. (My University, 2023)
Gamification, a new concept for adding game design elements to make activities more engaging is pervading many information systems. As a multidisciplinary research area, gamification integrates human motivation, technology, task characteristics and human computer interaction design. The motivation and fun surrounding gamified information systems (GIS) result from their potential benefits to institutions. However, a dearth of research and theory exists on how gamified interventions change behaviours in education, coupled with many challenges in conducting gamification research, particularly in developing economies (DE). Also, most of the GIS have been evaluated and adopted based on a one-size-fits-all approach. However, learners differ in their acceptance, motivation, engagement, and continuance use of technology. The thesis, therefore, examines the learner acceptance, engagement, and continuance use of GIS. Its purpose is to develop a theoretical and practical oriented framework for tailoring gamification to a target audience in higher education institutions (HEIs) in Ghana. To achieve this purpose, the study employed three theories, namely, the Unified Theory of Acceptance and Use of Technology (UTAUT), the Self- Determination Theory (SDT) and the Motivation-Opportunity-Ability (MOA). Posited in the tenants of the positivist research paradigm, 30 hypotheses were developed and tested through a quantitative survey by comparing their predictions with the observed gamified data collected from 442 participants in an HEI in Ghana. First, using the UTAUT theory, I investigated students’ (n=185) gaming experience, perception, and acceptance of adding game design elements to learning management systems (LMS) in HEIs in Ghana. The findings show that the learner characteristics necessary for technology acceptance encompass demographic features (age, gender), expectations (performance (PE), effort (EE)) and psychological components (social influence (SI), motivation) in Ghana’s higher education. The study found that institutional-based trust in existing technologies is a payoff to accepting new technologies. Prompting the need to reestablish trust in the digital era of accelerated innovation in education. The study further found that after the acceptance of the existing technologies (LMS), students' need to accept GIS is influenced by expected high performance, less effort, attitude, and the existence of social influence. Compared to the UTAUT model, this research found three typologies based on the significant factors in the data analysis that is critical for explaining behavioural intention and technology acceptance. The results from this study proved that two constructs (PE and EE) of the original UTAUT model may be considered as technology and learner attributes, while the remaining two (SI and facilitating conditions (FC)) may be considered as institutional factors or outcomes. A significant omission and less reliance in the conceptualisation of the original UTAUT model is the institutional-based trust (TR) and attitude (ATT). However, these factors produced a substantial improvement in the variance explained in technology acceptance and behavioural intention. Importantly, the extensions (TR and ATT) form the new psychological safety factors in the UTAUT model and serve as the necessary conditions for the uptake of information systems in DE. These typologies, hitherto missing in the original UTAUT model, suggested the concept of technology acceptance has gained prominence in HEIs in DE but in the context of technology and learner attributes, institutional factors, and psychological safety factors. Second, using the SDT, the study examined how game design elements support and enhance students’(n=124) basic psychological needs in learning and the need to clarify the role of autonomy, competence, and relatedness in GIS engagement. This study found three types of learning outcome measures (type of game elements, psychological need, and level of satisfaction) that is critical for a learner to make a decision and engage with the GIS. Importantly, feedback, interactivity and aesthetic appeal were identified as positive elements for maintaining and motivating engagement. The reward systems which include points, badges and leaderboards were found to be stronger than competition-based elements in motivating learning outcomes. In this regard, competition-based learning on gamified platforms is not a salient practice to enhance students learning outcomes. The study further showed that merely providing students with reward systems does not necessarily lead to user competence, and a higher level of satisfaction is associated with a higher level of learner engagement, thus reducing students’ turnover intention. Hence, a diverse and not a one-size-fits-all reward system should be tailored towards the individual learning progress. Third, to show the feasibility of the GIS approach in education, I applied the MOA framework and developed a model to examine students' continuance use behaviour. To demonstrate the importance of learner characteristics and outcomes of gamification, I conducted an evaluation (n=133) of a gamified version and investigated the efficacy of aesthetic experience, information technology capability, and information quality regarding learner continuance behaviours. The study found the opportunity ability motivation (OAM) framework as the appropriate interplay between learner characteristics, the platform, and the gamification elements. In applying the OAM framework, the findings suggest that for a behaviour change to take place, there is a need for an opportunity to experience it or try it (triability). However, for triability to lead to acceptance or intention to use, there should be ability to perform the behaviour and this ability includes learner characteristics and the ease of cognitive understanding of the GIS. Motivation therefore becomes an outcome because an opportunity has been created to perform the behaviour. The findings also revealed that self-expansion and meaning are the key determinants of aesthetic experience (appeal) of GIS. These new findings suggested that the concept of aesthetic experience, an aspect of both hedonic and utilitarian value has gained prominence in Ghana’s higher education. The result of this finding draws scholarly attention to aesthetic experience as a parsimonious yet powerful construct that compliments the notion of continuance use behaviour and engagement with GIS. The originality and contribution of the study to research and practice are as follows. First, the findings of the three objectives culminate into an Integrated Theoretical Model of HEIGamification Configuration (HEIGC) for tailoring gamification offerings in HEIs based on three clusters: Learner characteristics, Learner outcomes (critical decision stage) and Learner continuance behaviour. The model priorities for policymakers suggest that attitudes about accepting these types of platforms in education is primarily driven by their affordances i.e., psychological safety (autonomy, competence and social influence) and personality traits (PE, EE, Trust, aesthetic appeal and gamification elements) in DE HEIs. Second, this study addresses the limited results and evaluation of gamification and uncovers the efficacy of engaging and motivating learning behaviour change in Ghana and West Africa’s higher education. Hitherto absent in literature, this doctoral study addresses the lack of gamification research findings from the DE context. Third, the model provides eight theoretical constructs on acceptance, motivation, engagement, and outcomes of gamification, including a six-step practitioners’ guideline for tailoring gamification strategy to motivate HEIs to become more purpose-driven. The contribution of the study has resulted in three peer-reviewed articles, one book chapter and three full conference papers. The candidate has served the Association of Information Systems (AIS) and Gamification Community as the Vice President and Secretary of the Special Interest Group on Game Design and Research (AIS SIGGAME) since November 2019.
PhD. Information Systems
Keywords: Tailoring Gamified Information Systems; Higher Education Institutions; Developing Economy